2005
DOI: 10.1631/jzus.2005.b1182
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of chronic hepatitis B patients with YMDD mutation after lamivudine therapy

Abstract: Abstract:Objective: To study the clinical features of chronic hepatitis B (CHB) patients with tyrosine-methionine-aspartateaspartate (YMDD) mutation after lamivudine therapy. Methods: This investigation was a retrospective study of 63 CHB patients with YMDD mutation during lamivudine therapy. Clinical data, including period and types of YMDD mutation; hepatitis B virus (HBV) DNA levels and alanine aminotransferase (ALT) levels before and after YMDD mutation were measured. YMDD mutation in the HBV DNA polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…In a study by Li Zhou et al. , 16 some patients with YMDD motif mutants had significantly lower HBV DNA and ALT levels compared with baseline values, which might be due to decreased replication efficiency of the HBV mutants.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a study by Li Zhou et al. , 16 some patients with YMDD motif mutants had significantly lower HBV DNA and ALT levels compared with baseline values, which might be due to decreased replication efficiency of the HBV mutants.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, in patients maintaining HBV DNA level in the range of 2.6-5.0 log copies/mL and ALT < 20 IU/L, switching to dual therapy with adefovir in combination with lamivudine depends on the related viral breakthrough. In a study by Li Zhou et al, 16 some patients with YMDD motif mutants had significantly lower HBV DNA and ALT levels compared with baseline In patients treated with lamivudine for 3 years or more, the incidence of tyrosine-methionine-aspartateaspartate (YMDD) motif mutant by alanine aminotransferase (IU/L) level was 58% in 113 patients in group A, 60% in 84 patients in group B, and 80% in 37 patients in group C (P = 0.002), and that of BTH in the corresponding groups was 7%, 14%, and 57% (P < 0.001). (a) Incidence of YMDD mutants over time (P = 0.0015).…”
Section: Discussionmentioning
confidence: 99%
“…The only limitation, when compared to other anti-viral agents used in the treatment of chronic hepatitis B, is drug resistance, which may arise during lamivudine therapy. [7][8][9][10][11][12][13][14][15] Factors that may be associated with the development of lamivudine resistance in the literature have been reported as the patient's age, sex, body-mass index, HBeAg positivity, HBV genotype, pathological condition of the liver prior to treatment, pre-treatment serum ALT and HBV-DNA levels. 7,8,12,16 In this study, apart from the factors triggering the development of resistance mentioned in the literature, it has been investigated whether MDR1 gene polymorphism is associated with the development of lamivudine resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of efficacy generally increases over time post LAM treatment, from 14-47% after 1 year to 26-71% after 2 years, 49-57% after 3 years, and 67% after 4 years (Tsubota, 2006). Liu, et al found that the majority of the cases (42/63, 66.6%) with YMDD mutants were detected between 12 and 24 months post therapy (Liu et al, 2005). To the best of our knowledge, there is limited data in terms of the proportion and persistent time during YMDD mutants pathological process.…”
Section: Introductionmentioning
confidence: 99%